2020
DOI: 10.1016/j.addbeh.2019.106131
|View full text |Cite
|
Sign up to set email alerts
|

Parents modelling, peer influence and peer selection impact on adolescent smoking behavior: A longitudinal study in two age cohorts

Abstract: Understanding the key factors that influence smoking behavior, especially during adolescence, has a meaningful impact on public health. This study examined the impact of parent modelling, peer influence and peer selection on adolescent smoking behavior in two Portuguese cohorts followed for three years.A questionnaire was delivered in classes and schools randomly selected, three times, one per year (cohort1: time1-7th, time2-8th, time3-9th; cohort2: time1-10th, time2-11th, time3-12th graders).The sample includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
1
15
1
3
Order By: Relevance
“…Therefore, observed similarity among friends may be due to selection effects, socialization effects, or a combination of both. A three-wave longitudinal study of peer influences on adolescents' smoking behavior used a crosslagged design to separate selection from socialization effects and found evidence for both paths (Vitória et al 2020). Adolescents' smoking behavior in their younger cohort, similar in age to the present sample, predicted the choice of friend who smoked at Time 2, and friends' smoking behavior at Time 2 predicted participants' smoking behavior at Time 3.…”
Section: Studying Peer Effects On Prosocial Behavior In Classroom Commentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, observed similarity among friends may be due to selection effects, socialization effects, or a combination of both. A three-wave longitudinal study of peer influences on adolescents' smoking behavior used a crosslagged design to separate selection from socialization effects and found evidence for both paths (Vitória et al 2020). Adolescents' smoking behavior in their younger cohort, similar in age to the present sample, predicted the choice of friend who smoked at Time 2, and friends' smoking behavior at Time 2 predicted participants' smoking behavior at Time 3.…”
Section: Studying Peer Effects On Prosocial Behavior In Classroom Commentioning
confidence: 55%
“…A broad research literature has demonstrated the influence of peers on adolescents' behavior in a variety domains. The focus of this research has been on problem behaviors, such as smoking and drinking (Ragan 2020;Vitória et al 2020), problematic social media use (Marino et al 2020), and aggressive and antisocial behavior (Jung et al 2019).…”
Section: The Influence Of Peers On the Development Of Prosocial Behaviormentioning
confidence: 99%
“…This was reflected in both limitations to pupil knowledge compared with smoking and also in less evidence of bi-directional communication between child and micro-system levels, specifically parents and school, with children more likely to acquire e-cigarette knowledge from a user they know than either teachers or non-using parents. In later adolescence, while family function retains importance, peer influence assumes greater significance on attitudes and behaviours for smoking, 43 suggesting that communication from family at this age may be highly important in future outcomes. Absence of clear messaging on e-cigarettes within families and from schools means inevitable variations in pupil understanding that is more observable than for smoking, where curriculum content is established and harms are well-evidenced.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers found that intergenerational transmission, which influenced factors due to the lack of rules at home related to cigarettes (Vitória et al, 2020), lack of discussion of the dangers of smoking (Mak, 2018), and lack of parental supervision of children. Parents who smoke also have difficulty in keeping their children from smoking.…”
Section: The Effect Of Parental Influence On Smoking Behaviormentioning
confidence: 99%